2014
DOI: 10.9790/1959-03614855
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Health Education Program on Knowledge and Practices about Menstrual Hygiene among Adolescents Girls at Orphanage Home

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 14 publications
3
13
0
Order By: Relevance
“…Their understanding has been signicanty improved in the postintervention process. Such results were consistent with other studies conducted in Egypt, Saudi Arabia and India [10][11][12]. In our study, knowledge on cause of menstruation was poor among participants i.e.…”
Section: Methodssupporting
confidence: 93%
“…Their understanding has been signicanty improved in the postintervention process. Such results were consistent with other studies conducted in Egypt, Saudi Arabia and India [10][11][12]. In our study, knowledge on cause of menstruation was poor among participants i.e.…”
Section: Methodssupporting
confidence: 93%
“…[25] Regarding the medical and obstetric data, the age of menstruation, the present study findings revealed that the mean age of Damietta group was 13.4 ± 1.4 while the mean age of menstruation of Port Said was 11.1 ± 1.2. These findings are in agreement with several previous studies [27][28][29][30] in which the authors mentioned that mostly sixty-seven percent of the girls were well prepared and aware about menstruation.…”
Section: Discussionsupporting
confidence: 93%
“…These do not include indexes from three studies which collapsed across an unknown set of items [20,43,46]. Further, in two studies, authors included attending school or university, and participating in religious practices during menstruation [16], and food restrictions and exercise [18] as menstrual practices. These fit poorly with those reported as hygiene behaviours in other studies and are not included in Table 5.…”
Section: Menstrual and Hygiene Practicesmentioning
confidence: 99%